Uso dos serviços de saúde da Atenção Terciária por participantes e não-participantes de ações de promoção da saúde da Atenção Primária: estudo retrospectivo - Silva, Nayara Formenton da (Universidade Federal de São Carlos, 2018)
In view of the fast increase in the number of people affected by chronic no communicable diseases in Brazil and in the world, the provision of health promotion and disease prevention actions in health facilities in Primary Care becomes a convenient option for the population in order to promote healthier aging throughout life. Thus, participation in these actions can have a positive economic impact for users and for the public health system. In this context, the objective of this study was to analyze the association between the participation in preventive actions offered in Primary Care and the use of Tertiary Care health services. It was a quantitative, longitudinal and retrospective study, which identified preventive actions in all the health units of the municipality and analyzed the medical records and hospital records of the participants of the actions, in order to verify how they used the network tertiary level, compared to those who did not participate, with a sample of 496 people. Number of visits, number of diseases, number of hospitalizations and number of medications were analyzed. Descriptive and intergroup analysis were performed using the Statistical Package for the Social Science (SPSS) statistical package, with the Chi-square test for the categorical data and the Mann Whitney test for comparison between the groups. The mean age of the participant group was 60.6 years (SD ± 13.1) and the non-participant group was 60.4 years (SD ± 13.0). Of the 28 units analyzed, 71% had health promotion actions, divided into two categories: a) supervised body/manuals activities (40,6%); and b) oriented health education activities (59,4%). Of the 894 hospital visits analyzed, except for the number of exams, there was no statistically significant difference between the groups for the number of visits, urgency appointments, medications, hospitalizations, days of hospitalization and outpatient visits. It was concluded that there was no relation between participation in actions to promote health and use of hospital services.
Keywords: Ações preventivas; Atenção primária à saúde; Atenção terciária à saúde; Promoção da saúde; Preventive actions; Primary health care; Tertiary health care; Health promotion; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA